2006
DOI: 10.1002/anie.200503800
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Organization of Oriented Calcium Carbonate/Polymer Composites: Effects of a Matrix Peptide Isolated from the Exoskeleton of a Crayfish

Abstract: Gone fishing: Unidirectionally oriented CaCO3 crystalline films have been prepared on chitin matrices in the presence of calcification‐associated peptide (CAP‐1), which was isolated from the exoskeleton of the red swamp crayfish. The interactions of CAP‐1 with the matrix and the acidic nature of the peptide lead to a filmlike assembly of CaCO3 nanocrystals through transformation of amorphous calcium carbonate (see picture).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
129
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(133 citation statements)
references
References 48 publications
4
129
0
Order By: Relevance
“…A large number of examples of ordered macromolecular structures are also known in the world of biomacromolecules. Mesocrystal formation along a pre-structured organic matrix seems to be especially valid in biomineralization processes, as could also be demonstrated by biomimetic mineralization experiments [21][22][23][24][25] . Typical examples for a matrix-mediated nanoparticle growth are the formation and growth of bones as well as the growth of nacre [25][26][27] .…”
Section: Wang Et Al Prepared a Variety Of Eufmentioning
confidence: 81%
“…A large number of examples of ordered macromolecular structures are also known in the world of biomacromolecules. Mesocrystal formation along a pre-structured organic matrix seems to be especially valid in biomineralization processes, as could also be demonstrated by biomimetic mineralization experiments [21][22][23][24][25] . Typical examples for a matrix-mediated nanoparticle growth are the formation and growth of bones as well as the growth of nacre [25][26][27] .…”
Section: Wang Et Al Prepared a Variety Of Eufmentioning
confidence: 81%
“…[28][29][30] The crayfish exoskeleton is a Bio-inspired polymer-inorganic composites A Sugawara-Narutaki fascinating biomineral because of its remarkable mechanical properties. It consists mainly of chitin/protein microfibrils and CaCO 3 (calcite and ACC).…”
Section: Oriented Caco 3 Thin Filmsmentioning
confidence: 99%
“…33 Calcite thin films form in the presence of CAP-1 (3.0 Â 10 À3 wt%) on a chitin matrix. 28 The thin film is composed of nanocrystals with their c-axes oriented unidirectionally (Figures 5b-d). Real-time observation of CaCO 3 crystallization by polarizing optical microscopy drove us to speculate that the oriented film forms via amorphous-tocrystalline transformation.…”
Section: Oriented Caco 3 Thin Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kato and co-workers have reported that the cooperative effects of organic macromolecules facilitate the formation of organic/inorganic composites. [21][22][23][24][25][26][27][28] The goal of the present study is the development of rational molecular-control approaches for the direction of crystal growth, as observed in biomineralization.…”
Section: Introductionmentioning
confidence: 99%